Evaluation of the Use of Microalgae as a Novel Process for the Valorisation of Nutrient Rich Digestate in a Context of Circular Economy - FLEURIANE FERNANDES (2023)
Nutrient rich digestate resulting from the anaerobic digestion of waste from different feedstocks (kitchen waste, manure, agricultural waste, etc.) is mainly used in Northwest Europe as a fertiliser, but its heavy usage has led to soil eutrophication and its spreading onto arable land is now restricted under the Nutrient Vulnerable Zones policy. Consequently, digestate has become an underused resource and novel technologies to remediate this waste are now needed. In this thesis, microalgae were evaluated for their potential to bioremediate digestate, within the context of a circular economy. Chapter 1 presents a summary of digestate characteristics and its current use and discusses the circular economy concept focusing on microalgae as a bioremediation tool. Digestate is characterised by its dark colour and high dry matter content, which can be bottlenecks to light penetration and consequently microalgal growth, hence treatment is essential to allow for microalgal growth on this waste. Chapter 2 investigated mechanical and biological processing of a digestate from kitchen waste and aimed to assess its potential to support microalgal growth. Digestate was shown to be a suitable nutrient source for Chlorella vulgaris, following membrane filtration, which was highly efficient at separating liquid and solid fractions of digestate. 2.5% of digestate was the optimal concentration used in this work, as higher levels could lead to ammonium toxicity, therefore, this chapter also highlighted the bottlenecks of digestate utilisation for microalgal cultivation. To improve digestate uptake by microalgae, chapter 3 tailored different digestate sources to Chlorella vulgaris and Scenedesmus obliquus while maintaining a low pH to increase ammonium availability by reducing evaporation. Digestate from pig manure provided the best growth results in both strains, and while ammonium availability was increased, acclimation of strains to high ammonium levels was still necessary, limiting the use of high concentrations of digestate in cultures. Composition analysis of the microalgal biomass showed that nitrogen starvation, caused by higher pHs and reduced ammonium lead to lipid increase. This chapter demonstrated the importance of digestate and strain pairing to improve remediation and enhance scalability of valorising digestate within a circular economy. Growth of microalgae on digestate was demonstrated in chapters 2 and 3, to pursue the circular economy approach and use the produced biomass, chapter 4 subsequently aimed to assess the feasibility of using a microalgal hydrolysate derived from digestate as a feed ingredient in the feed of Nile tilapia. Enzymatic hydrolysis was used to alleviate palatability issues encountered when whole cells are incorporated into feed. An incorporation of 10% of the waste-derived hydrolysate did not convey advantages in terms of the fish growth but increased fatty acid content demonstrating a commercial advantage of the ingredient in terms of flesh quality. Increasing digestate uptake by microalgae is essential to increase viability of the circular economy concept presented in chapter 2, 3 & 4. Consequently, chapter 5 investigated the potential of microalgae-bacteria consortia for this purpose, by studying the bacterial community associated to Chlorella vulgaris and the influence of nutrient availability on this dynamic association. Sequencing analysis revealed that there was a likelihood of growth-promoting and other advantages conveyed by bacteria growing concomitantly with microalgae and the use of bacteria to increase digestate remediation by microalgae was discussed. The different lines of research investigated in this thesis demonstrated the feasibility of valorising nutrient rich digestate using microalgae by developing a circular economy approach. My thesis has also highlighted some of the bottlenecks to the establishment of a sustainable and commercially viable microalgal industry in the UK and globally, and additional research contributing to bridging this gap were discussed in Chapter 6, giving an outlook on future research prospects in the field of microalgae biorefineries.